STUDI KERENTANAN DAN ARAHAN MITIGASI BENCANA BANJIR DI KECAMATAN PURING KABUPATEN KEBUMEN TAHUN 2016 - Sri Muliana Mardikaningsih; Chatarina Muryani; Setya Nugraha (GeoEco, 2017)
The purpose of this research is to know: (1) the level of the flood vulnerability in Puring Subdistrict of Kebumen Regency. (2) Referral flood disaster mitigation in Puring Subdistrict of Kebumen Regency. The method that used on this research is a descriptive survey method with spatial approach. The population are the entire land units and individuals on the Puring subdistrict, as well as the Government. Samples of the research are the unit of land, individuals who were affected by flood at 12 northern parts of the village in Puring Subdistrict, and Disaster Relief Agencies of Kebumen Regency. The number of its units is 7. The sampling technique a population, purposive sampling, probability sampling. The data collecting techniques were interviews, observation, and documentation. Triangulation was used for the validity of the data. Used the overlay and skoring parameters of flood vulnerability level, i.e. land form, the slope of the slopes, soils, and land use for the data’s analyzing. Referral flood mitigation is determined based on the level of vulnerability and those type of flood. The results of these research are (1) the level of flood vulnerability in Puring consists of 3 classes, such as: (a) the Very Vulnerable class includes 12 villages in up to of 2,190.98 ha (80,43%) area; (b) Vulnerable Class includes 7 villages that’s covering of 530.67 ha (19,48%) area; (c) Less Vulnerable Class consists of 1 village in 2.57 ha (0.09%) of the area. (2) Referral flood mitigation is divided into 4 types, i.e. Type I for very vulnerable and the flood of submissions, Type II for vulnerable level and type of flood of submissions, Type III for vulnerable level and the type of local flood, Type IV class is for less susceptible level and flood of submissions type. Key Words: Flood, Vulnerability, Mitigation